2008
DOI: 10.1088/0953-4075/41/3/035703
|View full text |Cite
|
Sign up to set email alerts
|

EUV spectroscopy of Xe ions from the large helical device at the National Institute for Fusion Science for stable plasmas and plasmas undergoing radiation collapse

Abstract: We have observed EUV spectra of xenon ions from the large helical device (LHD) at the National Institute for Fusion Science in Toki in the wavelength range of 10-17 nm using a high resolution SOXMOS spectrometer. A small quantity of xenon gas was injected into the large helical device. In some cases, the plasma evolution was stable and a steady discharge was obtained for several seconds, but sometimes the plasma underwent radiation collapse and rapid cooling and in this situation the EUV yield was significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…In earlier experiments on Sn and Xe injection in the LHD, it was noted that for the majority of ion stages, only resonance transitions to the ground configuration were observed but a notable exception in each case was provided by Cu-like Sn and Xe ions [22,27,28]. Cu-like ions have a single 4s electron outside a closed n = 3 shell.…”
Section: +mentioning
confidence: 99%
“…In earlier experiments on Sn and Xe injection in the LHD, it was noted that for the majority of ion stages, only resonance transitions to the ground configuration were observed but a notable exception in each case was provided by Cu-like Sn and Xe ions [22,27,28]. Cu-like ions have a single 4s electron outside a closed n = 3 shell.…”
Section: +mentioning
confidence: 99%
“…The EUV spectra were recorded by a grazing incidence spectrometer SOXMOS [39] whose groove density and focal length were 600 mm collapse [24,41,42]. The spectrometer was carefully calibrated by observing carbon, boron and neon lines whose wavelengths are well known following neon injection (carbon and boron lines are always present as impurities in the LHD).…”
Section: Figure 1: Time Sequences Of Neutral Beam Injection (Nbi Heamentioning
confidence: 99%
“…Biedermann et al [5] observed lines in EBIT spectra for Rb-like Xel7+ to Cu-like Xe25+. Kato et al [6] measured EUV spectra of xenon ions from the large helical device (LHD). Crespo et al [7] measured transitions in highly charged ions of Kr, Xe, and Ba at the Lawrence Livermore National Laboratory EBIT.…”
Section: Introductionmentioning
confidence: 99%